PENINGKATAN KAPASITAS KELEMBAGAAN DAN PENGELOLAAN TERNAK BAGI PETERNAKAN KAMBING DI KECAMATAN TOARI KABUPATEN KOLAKA - Husnaeni, Husnaeni; Purbaningsih, Yuli; Nursalam, Nursalam; Helviani, Helviani; Bahari, Doddy Ismunandar; Masitah, Masitah; Handayani, Fitrianti; Wilhan J, Aan; Marlina, Marlina; Yusuf, Muhammad; Zulkharnanim, Zulkharnanim; Noor, Aulia Uswa (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
The community service program in Toari District, Kolaka Regency aims to increase institutional capacity and management of goat livestock. By identifying the needs and challenges of breeders, a comprehensive training and mentoring program was developed. Training includes livestock management, selection of superior seeds, feed management, livestock health care, financial management and marketing. Regular mentoring provides continuous support to farmers after training is completed, so they can implement the skills and knowledge they have acquired into their daily farming practices. The results of implementing this program show a significant increase in farmers' understanding and skills regarding goat management. Farmers become better able to recognize and deal effectively with livestock health, nutrition and reproductive problems, which in turn improves livestock welfare and livestock business productivity. Apart from that, the increase in the welfare of farmers can also be seen from the increase in their income and ability to manage livestock businesses efficiently. This program has also succeeded in strengthening cross-sector collaboration between the government, educational institutions and other stakeholders. This collaboration is the basis for the sustainability of the goat farming sector in the region, because it allows for the exchange of knowledge, resources and support between various related parties